Memposisikan Islam Sebagai Agama Moralitas - Abdul Chalim (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2019)
In this global era there are many thought that moralities just a norm which consists in the point that given in the society. It means that there is no criterion directed as system's reference for moral that is admissible by society in a general. Thus, morals' societies that will be accepted by another society are less showed. Islam comes as religion that raised a high morality. In all decade its trip, Islam has proven that the rule which is include in the all class is not all different. Islam teaches how the human have to interact by another human, moslem humanity attitude or even non moslem etc. Therefore, Islam can unite people with global morality teaching admissible by all common society. Keywords : Islam, Religion, Morality